HUBUNGAN FAKTOR SOSIO-DEMOGRAFI SERTA PERILKU PRA DAN PASCA PERSALINAN DENGAN KEMATIAN BALITA - Santiyasa, M.Si, Drs. I Wayan (Jurnal Studi Jender SRIKANDI, 2012)
This reserch aim to find out and to what extent socio-demographic factors as well as pre and post delivery activities both separately and simultaneously are correlated with infant and child mortality. It furtherseeks to discover from the factors observed which of them has the most dominant correlation with infant and child mortality. The step taken to achieve the above aim is ti find the correlation index between the mother?s level of education, her age when giving birth, spans between childbirth, frequency of childbirth, pre and post delivery activities and incidence of infan and child mortality by using logit regression. The correlation index (r) and determination index(R) indicates the extent of the correlation and the contributing of the observed factors to infant and child mortality.The result of the reserch are as follows: the mother?s age when giving birth, spans between childbirth, pre and post delivery activities are most correlated with infant and child mortality.
Keywords: Infant and child mortality, logit regrresion